Proceedings of the 3rd ACM Workshop on Cloud Computing Security Workshop 2011
DOI: 10.1145/2046660.2046670
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of L2 cache covert channels in virtualized environments

Abstract: Recent exploration into the unique security challenges of cloud computing have shown that when virtual machines belonging to different customers share the same physical machine, new forms of cross-VM covert channel communication arise. In this paper, we explore one of these threats, L2 cache covert channels, and demonstrate the limits of these this threat by providing a quantification of the channel bit rates and an assessment of its ability to do harm. Through progressively refining models of cross-VM covert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
133
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(134 citation statements)
references
References 19 publications
(15 reference statements)
1
133
0
Order By: Relevance
“…Ristenpart et al [5] showed that the IP machine naming conventions of cloud providers allowed adversarial users to narrow down where a victim VM resided in a large-scale cluster. Xu et al [10] and Herzberg et al [8] extended this study, resulting, in part, in cloud providers changing their naming conventions, reducing the effectiveness of network topology-based co-residency attacks. Following this evolution Varadarajan et al [9] evaluated the susceptibility of three cloud providers to VM placement attacks, and showed that techniques like virtual private clouds (VPC) render some of them ineffective.…”
Section: Related Workmentioning
confidence: 99%
“…Ristenpart et al [5] showed that the IP machine naming conventions of cloud providers allowed adversarial users to narrow down where a victim VM resided in a large-scale cluster. Xu et al [10] and Herzberg et al [8] extended this study, resulting, in part, in cloud providers changing their naming conventions, reducing the effectiveness of network topology-based co-residency attacks. Following this evolution Varadarajan et al [9] evaluated the susceptibility of three cloud providers to VM placement attacks, and showed that techniques like virtual private clouds (VPC) render some of them ineffective.…”
Section: Related Workmentioning
confidence: 99%
“…Shared resources, such as caches [27], CPU [28], network subsystems [29], [30], or memory management [31], [32], are not only prevalent in all modern systems, but also run the risk of being the conduit for covert channel communication.…”
Section: A Covert Channel Backgroundmentioning
confidence: 99%
“…In [34], the research focused on threats on the L2 covert channels and how these threats can be exploited or countered.…”
Section: Side-channel Attacksmentioning
confidence: 99%